Tumor specific regulatory T cells in the bone marrow of breast cancer patients selectively upregulate the emigration receptor S1P1 - Rathinasamy, Anchana; Domschke, Christoph; Ge, Yingzi; Böhm, Hans-Henning; Dettling, Steffen; Jansen, David; Lasitschka, Felix; Umansky, Ludmila; Hartmann, Jennifer; Herold-Mende, Christel; Schütz, Florian; Beckhove, Philipp (Cancer immunology immunotherapy, 2017)
Regulatory T cells (Treg) hamper anti-tumor T-cell responses resulting in reduced survival and failure of cancer immunotherapy. Among lymphoid organs, the bone marrow (BM) is a major site of Treg residence and recirculation. However, the process governing the emigration of Treg from BM into the circulation remains elusive. We here show that breast cancer patients harbour reduced Treg frequencies in the BM as compared to healthy individuals or the blood. This was particularly the case for tumor antigen-specific Treg which were quantified by MHCII tumor peptide loaded tetramers. We further demonstrate that decreased Treg distribution in the BM correlated with increased Treg redistribution to tumor tissue, suggesting that TCR triggering induces a translocation of Treg from the BM into tumor tissue. Sphingosine-1-phosphate receptor 1 (S1P1)—which is known to mediate exit of immune cells from lymphoid organs was selectively expressed by tumor antigen-specific BM Treg. S1P1 expression could be induced in Treg by BM-resident antigen-presenting cells (BMAPCs) in conjunction with TCR stimulation, but not by TCR stimulation or BMAPCs alone and triggered the migration of Treg but not conventional T cells (Tcon) to its ligand Sphingosine-1-phosphate (S1P). Interestingly, we detected marked S1P gradients between PB and BM in breast cancer patients but not in healthy individuals. Taken together, our data suggest a role for S1P1 in mediating the selective mobilization of tumor specific Treg from the BM of breast cancer patients and their translocation into tumor tissue.
Gesehen am 06.04.2018